Autoimmune Heparin-Induced Thrombocytopenia after Transcatheter Aortic Valve Implantation: Successful Treatment with Adjunct High-Dose Intravenous Immunoglobulin - Bakchoul, Tamam; Borst, Oliver; Riessen, Reimer; Lucic, Josip; Gawaz, Meinrad; Althaus, Karina; Aidery, Parwez (TH Open, 2019)
We describe a rare case of autoimmune heparin-induced thrombocytopenia after transcatheter aortic valve implantation in which antibodies against platelet factor 4/heparin have led to platelet activation even after heparin cessation, causing a delayed drop in platelet count to below 20 × 109/L. Most interestingly, platelet count rapidly improved after intravenous immunoglobulin treatment and no new thromboembolic complications were observed with further anticoagulation with rivaroxaban.
Keywords: thrombocytopenia; heparin; antibody